Design of Filter Bank Transmultiplexer System for Communication Using Different Modulation Technique - Mir, Zaffer Iqbal; Sheikh, Javiad Ahmad; Amin, Mehboob ul; Bhat, G.M (International Journal of Computer Sciences and Engineering, 2019)
In this paper, design and comparative analysis outline strategy for trans-multiplexer (TMUX) system for communication with different windowing techniques are analyzed. In this scheme four adjustable window techniques viz., Blackman window, Saramaki window, Kaiser Window and ultra-spherical windows with different modulation techniques are used for designing a multi-channel filter bank trans-multiplexer FB-TMUX. A comparative study of performance of these four windowing functions with different modulation techniques such as Cosine, sine, complex and Extended lapped transform (ELT) for the recommended roll-off factor (RF) and stop band attenuation (As) is designed for trans-multiplexer is presented. The objective functions of the design to reduce Inter-symbol-interference (ISI) and specifically inter-channel-interference (ICI).